Evaluation of Public Infrastructure: A Case of Sapon Dam Kulon Progo, Indonesia - Nuni Budi Prastiwi; Akhmad Makhfatih; Inayati Nuraini Dwiputri (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2017)
One of problems in making a government’s balance sheet is to determine the value of infrastructure run by the government. It is because the infrastructure is valueless and closely similar in characteristics to public goods. In general, most researchers would use travel cost method to value government infrastructure. Yet, this method is very sensitive toward respondents’ characteristics and in many cases, it results in over estimated valuation. Meanwhile, a valuation technique using cost approach for government infrastructure reflects less its benefits and in many cases, it also tends to be undervalued.Against the aforementioned issue, this research attempted to evaluate state-owned infrastructure using a capitalization method. The object of this research was Sapon Dam located in Kulon Progo Regency, Indonesia. This dam is a state-owned asset functioned to sustain agricultural development particularly for irrigating paddies. This research was aimed at estimating the value of Sapon Dam using a capitalization method. In this method, the absence of infrastructure value was replaced with difference-in-differences analysis for proxy income.The data used in this research was secondary data which included paddy planting areas in irrigated and rain-fed fields, and also farmers’ net income. It was found that the estimated value of Sapon Dam per December 15th2015 was IDR 96,659,385,018.72.